2017
DOI: 10.1016/j.ijpharm.2017.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Skin vaccination using microneedles coated with a plasmid DNA cocktail encoding nucleosomal histones of Leishmania spp.

Abstract: Vaccine delivery using microneedles (MNs) represents a safe, easily disposable and painless alternative to traditional needle immunizations. The MN delivery of DNA vaccines to the dermis may result in a superior immune response and/or an equivalent immune response at a lower vaccine dose (dose-sparing). This could be of special interest for immunization programs against neglected tropical diseases such as leishmaniasis. In this work, we loaded a MN device with 60μg of a plasmid DNA cocktail encoding the Leishm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…In another study, MNs were coated with 60 μg of a plasmid DNA cocktail encoding the Leishmania infantum nucleosomal histones H2A, H2B, H3 and H4 and their immunization capacity was compared against subcutaneous or intradermal injection of the plasmid. The results demonstrated that MNs improved immunogenicity, but higher plasmid doses might be required for better Leishmania control (Moreno et al, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…In another study, MNs were coated with 60 μg of a plasmid DNA cocktail encoding the Leishmania infantum nucleosomal histones H2A, H2B, H3 and H4 and their immunization capacity was compared against subcutaneous or intradermal injection of the plasmid. The results demonstrated that MNs improved immunogenicity, but higher plasmid doses might be required for better Leishmania control (Moreno et al, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…the minimum time, it provided confidence that the entire MN cargo was deposited in skin following removal of the device from the tissue. A range of application times (<3 minutes to 1 hour) have been reported for MN coated APIs in murine, guinea pig and rat skin (Cormier et al 2004;Kim et al 2010;Chong et al 2013;Ameri et al 2014;Moreno et al 2017;Shakya et al 2017) and delivery efficiencies vary widely (37->90%). The duration of application required for MN delivery systems is determined, in part, by the solubility of the API and the coating formulation (Zhao et al 2016;Zhao et al 2017), and so poorly soluble macromolecular therapeutics, such as plasmid DNA, may require extended application times (Moreno et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Up to a length of 500 μm, application of MNs is painless as they are too short to activate nerves in the dermis. MNs have been successfully used for intradermal delivery of DNA [ 63 ], siRNA [ 64 ], proteins [ 65 , 66 ], and peptides [ 67 ]. Especially hollow MNs seem promising for the topical delivery of nucleic acids [ 61 ].…”
Section: Delivery Of Gene Therapies To the Skinmentioning
confidence: 99%